Residual efficacy of deltamethrin as assessed by rapidity of knockdown of Tribolium castaneum on a treated surface: Temperature and seasonal effects in field and laboratory settings. (March 2018) - Arthur, Frank H.
Abstract: Concrete arenas were treated with the pyrethroid deltamethrin at rates of 8, 16, and 24 mg active ingredient [AI]/m 2, and held either in a chamber set at 27 °C, inside a non-climate controlled interior building, or the floor of an empty grain bin. Bioassays of the arenas were conducted post-treatment by exposing mixed-sex adult Tribolium castaneum Herbst and assessing knockdown every 30 min for 3 h. Four separate trials were conducted, two during Autumn of 2015 and 2016 and two during Summer of 2016 and 2017. Knockdown did not increase with increasing application rate. Equations were fit to the combined rate data at each residual bioassay week for each location, and mean data were also compared to determine differences in knockdown at different times among the arenas held in the different locations. During Summer, knockdown was generally slower after two weeks on arenas held inside the grain bin compared to arenas held inside the building or inside the chamber. The arenas inside the bin experienced more hours of temperature above 32.2 °C during Summer compared to arenas inside the building or chamber. These extra hours of high temperature accumulation could have contributed to increased degradation of the residues, resulting in slower knockdown. During Autumn rapidity of knockdown was generally similar on arenas held in all three locations. In all trials, the total hours of temperature accumulation were far greater in the chamber compared to the building or the grain bin, but this had little effect on efficacy. Managers can use this information to more precisely apply deltamethrin, either as a pre-binning treatment inside a grain bin or elevator silo or as a residual treatment inside a milling or production facility. Highlights: Extreme high temperatures lead to increased degradation of deltamethrin. Efficacy assessment through rapidity through knockdown was an appropriate methodology for assessing residual efficacy. Temperature had less effect on deltamethrin degradation during Autumn compared to Summer.